Peran Literasi Keuangan, Locus of Control, Dan Financial Technology Dalam Mendorong Inklusi Keuangan UMKM - Iqram Iqram; Sahrir Sahrir; Rifqa Ayu Dasila (Pusat Riset dan Inovasi Nasional, 2025)
MSMEs play an important role in the economy, supported by financial literacy, locus of control, and financial technology. This research aims to analyze the influence of financial literacy, locus of control, and financial technology on the financial inclusion of Micro, Small and Medium Enterprises (MSMEs) in Palopo City. Financial literacy reflects an individual's understanding and ability to manage finances, while locus of control describes a person's level of control over financial events that affect their life. On the other hand, the adoption of financial technology plays a role as a facilitator in increas-ing access to financial services. This research uses quantitative methods with a population of 14.870 and data collection through questionnaires distributed to 120 MSMEs in Palopo City. The research results show that financial literacy, locus of control, and financial technology have a significant influ-ence on financial inclusion. Financial literacy factors and the use of financial technology are the main drivers in increasing the accessibility of financial services, while locus of control contributes to better financial decision making. These findings provide important implications for developing strategies for empowering MSMEs through increasing financial literacy, understanding locus of control, and more optimal integration of financial technology.